2017
DOI: 10.15740/has/irjaes/8.1/1-7
|View full text |Cite
|
Sign up to set email alerts
|

Economics of wheat production

Abstract: :In this study, an attempt has been made to study analysis of yield gap in wheat in Amravati district with view to study the economics of wheat production and resource use efficiency. The study was based on primary data on input used and there upon costs was collected from two tehsils viz., Amravati and Morshi and from each tahsil 45 samples were selected. Per hectare input utilization for wheat indicated that the medium farmers were used higher inputs as compared to other farm size group of farmers. Per hecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Agam et al (2019) reported similar findings in her study on growth performance of wheat in Amravati district during 1983-84 to 2012-13 and Sahu et al (2020) also reported similar findings in her research work on growth in production of wheat in India during 2000-01 to 2017-18.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Agam et al (2019) reported similar findings in her study on growth performance of wheat in Amravati district during 1983-84 to 2012-13 and Sahu et al (2020) also reported similar findings in her research work on growth in production of wheat in India during 2000-01 to 2017-18.…”
supporting
confidence: 75%
“…It compares well with other cereal in nutritive value. It has good nutrition profile with 12.1 per cent protein, 1.8 per cent lipids, 1.8 per cent ash, 2.0 per cent educing sugar, 6.7 per cent pentose, 59.2 per cent starch with good source of mineral of vitamin and nicotinic acid (Agam et al 2017). It is processed in different forms like flour, suzi, maida and being eaten by number of consumers in different ways as porridge (Halwa), chapati, bread and biscuits etc.…”
mentioning
confidence: 99%
“…It compares well with other cereals in nutritive value. It has a good nutrition profile with 12.1% protein, 1.8% lipids, 1.8% ash, 2.0% reducing sugar, 6.7% pentose, 59.2% starch, and a good source of minerals, vitamins, and nicotinic acid" [1]. It is processed in different forms like flour, Suzi, and maida, and is eaten by consumers in different ways such as porridge (Halwa), chapati, bread, and biscuits.…”
Section: Introductionmentioning
confidence: 99%
“…is a cereal grain, originated from the Southwest Asia, but now cultivated worldwide. It has been described as the "King of Cereal" (Agam et al, 2017). It can be grown from below sea level to 5000 m altitude and in areas where rainfall ranges between 300-1130 mm ( Kumar et al, 2014).…”
mentioning
confidence: 99%